The Great Disruption: How Machine Intelligence Will Transform the Role of Lawyers in the Delivery of Legal Services - J. O. Mcginnis; R. G. Pearce (Russian Journal of Economics and Law)
Objective: to analyze the influence of machine intelligence on legal practice and services.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, state and legal modeling.Results: The market for electronic legal services is at a relatively early, yet significant, stage in terms of the disruptive effect of machine intelligence in undermining lawyers' monopoly. As machine intelligence in lawyering develops exponentially, it will take an increasingly larger role in legal practice. Eventually, machine intelligence will prove faster and more efficient than many lawyers in providing those services. Lawyers will continue to provide services that cannot be commoditized if they are superstars, practice in highly specialized areas of law subject to rapid change, appear in court, or provide services where human relationships are central to their quality. Otherwise, no effective barriers to the advance of machine lawyering in legal practices exist - not even in the law and ethics of lawyering. Lawyers will continue to embrace machine intelligence as an input and fail to prevent non-lawyers from using it to deliver legal services. Ultimately, therefore, the disruptive effect of machine intelligence will trigger the end of lawyers' monopoly and provide a benefit to society and clients as legal services become more transparent and affordable to consumers, and access to justice thereby becomes more widely available. Scientific novelty: for the first time, the authors formulate the five areas of legal practice which will significantly change in the nearest future under the influence of machine intelligence: (1) discovery, (2) legal search, (3) generation of documents, (4) creation of briefs and memoranda, and (5) predictive analytics. Machine intelligence has already begun to significantly compete with lawyers and undermine their monopoly. Today, sizeable financial industries use machine intelligence to deliver legal services, even though the most economically significant developments have occurred in only three of the five areas identified above. The three areas that have proven most profitable are legal research, discovery, and document generation. Practical significance: the key results and conclusions of the research can be used in scientific, educational and law-enforcing activities when considering the issues related to the influence of machine intelligence on legal practice and services.